A DYE-TRACING TEST AS AN AID TO STUDYING KARST DEVELOPMENT AT AN ARTESIAN LIMESTONE SUB-AQUIFER: ZAGROS ZONE, IRAN - Mohammadi Z.; Raeisi E.; Zare M. (My University, 2007)
A dye-tracing test is employed to study the karst development and flow regime at an artesian limestone sub-aquifer, the Khersan3 Dam site, Zagros Zone, Iran. Tracer breakthrough curves showed an early dominant peak followed by a pronounced tailing effect. The peak concentration was a response to induced pressure during dye injection. The results suggest that the dye was pushed into the small pores and fissures around the injection point during dye injection. Hence, the dye moved out as a result of matrix and fissure diffusive processes and created a long pronounced tailing. The maximum flow velocity in the upper artesian sub-aquifer ranged from 0.97 to 2.9 m/h. However, the mean tracer velocity ranged from 0.19 to 0.51 m/h based on the mean residence tracer time; consequently, the flow regime in the artesian sub-aquifer was determined to be mainly diffusive. The results reveal (1) a low hydraulic gradient from upstream of the dam axis to downstream; consequently, there is no considerable flow; (2) poor karst development and diffuse flow at the tracing test area; (3) a discharge zone at a location downstream of the dam axis which is the main terminal of general flow direction at the dam site.
Keywords: ARTESIAN SUB-AQUIFER; DYE TRACING; IRAN; KARST DEVELOPMENT; ZAGROS ZONE